2017
DOI: 10.1007/s11427-016-9072-6
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic growth promoter olaquindox increases pathogen susceptibility in fish by inducing gut microbiota dysbiosis

Abstract: Low dose antibiotics have been used as growth promoters in livestock and fish. The use of antibiotics has been associated with reduced pathogen infections in livestock. In contrast, antibiotic growth promoter has been suspected of leading to disease outbreaks in aquaculture. However, this phenomenon is circumstantial and has not been confirmed in experimental conditions. In this study, we showed that antibiotic olaquindox increased the susceptibility of zebrafish to A. hydrophila infection. Olaquindox led to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 40 publications
3
46
0
1
Order By: Relevance
“…Studies from other sh species have also demonstrated the notable effects that antibiotics may have on the gut microbiota. For example, a loss of gut diversity was observed in Atlantic salmon following oxytetracycline treatment [62], in channel cat sh (Ictalurus punctatus) following orfenicol treatment [63], in fathead minnow (Pimephales promelas) after triclosan use [64] and in zebra sh following olaquindox treatment [65]. In contrast, in some cases, it has been reported that antibiotic treatment may even increase or cause a shift in species diversity, as shown for Atlantic salmon and zebra sh [12,13], and pacu (Piaractus mesopotamicus) [8] respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other sh species have also demonstrated the notable effects that antibiotics may have on the gut microbiota. For example, a loss of gut diversity was observed in Atlantic salmon following oxytetracycline treatment [62], in channel cat sh (Ictalurus punctatus) following orfenicol treatment [63], in fathead minnow (Pimephales promelas) after triclosan use [64] and in zebra sh following olaquindox treatment [65]. In contrast, in some cases, it has been reported that antibiotic treatment may even increase or cause a shift in species diversity, as shown for Atlantic salmon and zebra sh [12,13], and pacu (Piaractus mesopotamicus) [8] respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, different studies have demonstrated that highly diverse gut communities are more likely to protect the host from pathogens [43, 44]. This constitutes the base for the paradoxical negative health effect associated with the massive utilization of antibiotics in aquaculture: the reduction in microbial diversity facilitates colonization by opportunistic pathogens [45]. While this advocates for practices leading to enrichment of fish microbial communities to minimize pathogenic invasions in aquaculture [16], our results demonstrate that resistance to a bacterial pathogen can also be achieved by a single bacterial strain in a low complexity microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic administration has been associated with disease outbreaks in aquaculture (Cabello et al., 2013). The mechanism of microbiota dysbiosis triggered by prophylactic use of antibiotics was validated in zebrafish, where a low dose of olaquindox increased the susceptibility to Aeromonas hydrophila infection (He et al., 2017). Last, but not least, nutrition is an important factor driving microbiota assemblage and functional activity, as it directly impacts the host development and physiology (reviewed in Miles & Calder, 2015).…”
Section: Changes In the Selective Context Along The Production Chainmentioning
confidence: 99%